1993
DOI: 10.1017/s0022215100123278
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment and ear pathology in Nepal

Abstract: A stratified random cluster sample of 15,845 subjects was performed in two regions of Nepal to determine the prevalence and main causes of hearing impairment (the most common disability) and the prevalence of ear disease. Subjects reporting current ear pain, or ear discharge, or hearing impairment on direct questioning by a Nepali health worker (primary screening failed), had otoscopy and audiometry (using the Liverpool Field Audiometer) performed, and a questionnaire administered relating to past history. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…In Bangladesh, prevalence rate of 0.3% for severe hearing loss was reported in a normal school population [41]. In Nepal, the prevalence rate for hearing impairment greater than 30 dB in the general population was 16.6% [42].…”
Section: Prevalence/incidence Of Pcehl In the Developing Worldmentioning
confidence: 99%
“…In Bangladesh, prevalence rate of 0.3% for severe hearing loss was reported in a normal school population [41]. In Nepal, the prevalence rate for hearing impairment greater than 30 dB in the general population was 16.6% [42].…”
Section: Prevalence/incidence Of Pcehl In the Developing Worldmentioning
confidence: 99%
“…However, other authors have reported significant levels of ear disease in this region. In a robust study, Little et al 4 calculated that 7.4 per cent of the Nepalese population had tympanic membrane pathology, comparing unfavourably with an estimated UK prevalence of chronic otitis media of 4.1 per cent. 6 Interestingly, Little's group found a very similar rate of cholesteatomatous disease (24 per cent) to that seen in our study, and a similar value In addition, we must acknowledge the risk of confounding factors in our study, due to the nature of the ear camps from which our data were drawn.…”
Section: Discussionmentioning
confidence: 99%
“…1 In Nepal, approximately 16% of the population suffers of hearing loss and most of the hearing impairment in the school age group (55.2 per cent) is associated with otitis media or its sequelae. 2 A study by B P Koirala institute of health sciences in the Sunsari district found the prevalence of otitis media to be 10.3%. 3 A 13.2% prevalence of otitis media in children in the Morang district of Eastern Nepal has been reported in a study.…”
Section: Introductionmentioning
confidence: 99%